(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2019)
The present research aims to present a theoretical framework for the application of takaful insurance in Iraq, as well as to identify the level of impact on the development of insurance services in the Iraqi market, and to make recommendations and suggestions that lead to increased interest in this area, and thus contribute to the development and integration of insurance service in the Iraqi market, The research adopted the descriptive analytical method, and the questionnaire was used to survey the opinions of the research sample consisting of department managers and their assistants and some employees of the graduate degrees in addition to employees of the departments of electronic calculator in the Iraqi insurance sector, and then analyze the results of the answers of the research sample through the program (spss) According to statistical methods. The research reached a number of conclusions, most notably: the need for the Iraqi insurance market to establish a Takaful insurance company in order to achieve integration and diversity in insurance services provided. The research recommended a number of recommendations, the most important of them: the need to establish a Takaful insurance company in Iraq in order to provide Takaful insurance services, and the establishment of seminars and training programs to demonstrate the concept of the mechanism and the work of Takaful insurance companies and their importance.